EKOMODERNITAS ISLAM: Kepemimpinan, Mobilisasi dan Gerakan Lingkungan Hidup di Dua Pesantren di Jawa Barat - Wardatul Adawiah; Arya Hadi Dharmawan; Satyawan Sunito (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
This study explains how the AtQ, Garut Islamic boarding school and Mf H, Tasikmalaya Islamic boarding school approachs education through ecotheology which is carried out in response to the environmental crisis. The case boarding schools studied contained two environmental leadership and ecomodernity movements as well as santri pioneering in strengthening the local economy which had a different type. This study took two case boarding schools in West Java, namely the AtQ Ecology Islamic Boarding School, Garut and the MfH Islamic Boarding School, Tasikmalaya. This study aims to describe the process of leadership formation, resource mobility in the environmental movement which is integrated with strengthening the local economy in both Islamic boarding schools andthe role of santri alumni who have returned to the rural society. This study was conducted using a qualitative approach with a grounded theory method that is oriented to data from in-depth interviews, supported by field observations, documentation studies and literature studies. Result the research indicated that the environmental leadership of santri alumni was conduct from the tradition of Islamic ecotheology education in pesantren. The environmental movement carried out by pesantren is by utilizing a network of actors from various parties in mobilizing resources. Ecomodernity in the two pesantren has a different style. This is reflected in the alumni activities of AtQ, Garut students as pioneers of the environmental movement and local economic empowerment in the rural society through environmental education tours and advocacy. Meanwhile, the alumni of MfH students, Tasikmalaya, carry out da’wah on organic agriculture through the millennial santri farmer program and the agribusiness madrasa program.